Fashion, identity, image - Jobling, Paul (Bloomsbury Visual Arts, 2022)
"Uses influential fashion collections and shows to explore the huge shifts in identity, body politics, representation and authenticity in relation to clothing in Britain, Europe and America over the last 30 years"--
Keywords: Geschichte 1990-2020; Identität; Körperbild; Mode; USA; Europa; Fashion / Social aspects / Western countries / Case studies; Fashion / Political aspects / Western countries / Case studies; Identity politics / Western countries / Case studies; Intersectionality (Sociology) / Western countries / Case studies; Body image / Western countries / Case studies; Fashion writing / Western countries / Case studies; Advertising / Fashion / Western countries / Case studies; Advertising / Fashion; Body image; Fashion / Political aspects; Fashion / Social aspects; Fashion writing; Identity politics; Intersectionality (Sociology); Western countries; Case studies